"The Death of Ivan Ilich" An Electronic Study Edition of the Russian Text - Jahn, Gary R. (Open textbook library., 2020)
The Russian text of "The Death of Ivan Ilich" is presented for study in various formats: accompanied by an English translation; fully glossed, with explanatory and interpretive annotations; and supplemented by introductory remarks and an extensive bibliography.